2020
DOI: 10.21833/ijaas.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of entrepreneurship education on attitude, subjective norm and self-efficacy among undergraduates

Abstract: The Malaysian government recognized the importance of entrepreneurship's role in developing innovation and knowledge as new engines that could help the Malaysia economy to grow. Entrepreneurship education has become popular for developing economies and creating job opportunities in Malaysia. Entrepreneurship contributes significantly to economic growth; it increases job opportunities, nurtures innovation, and organization productivity. Most of the higher education institutions (HEI) in Malaysia are also engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Departing from the low interest of students in entrepreneurial activities, this study aims to measure the effectiveness of the RPC learning model based on the entrepreneurial values of the Madurese ethnic group towards increasing student entrepreneurial interest. The results of this study indicate that attitudes toward entrepreneurship, subjective norms, and self-efficacy are predictors of interest in entrepreneurship (Balder et al, 2020;Fenech et al, 2019;Mahmoud et al, 2020;Sudarmiatin & Hermawan, 2020). These results are to the suggested relationship between variables in the theory of planned behavior (Planned Behavior Theory).…”
Section: Introductionmentioning
confidence: 65%
“…Departing from the low interest of students in entrepreneurial activities, this study aims to measure the effectiveness of the RPC learning model based on the entrepreneurial values of the Madurese ethnic group towards increasing student entrepreneurial interest. The results of this study indicate that attitudes toward entrepreneurship, subjective norms, and self-efficacy are predictors of interest in entrepreneurship (Balder et al, 2020;Fenech et al, 2019;Mahmoud et al, 2020;Sudarmiatin & Hermawan, 2020). These results are to the suggested relationship between variables in the theory of planned behavior (Planned Behavior Theory).…”
Section: Introductionmentioning
confidence: 65%
“…Stronger EE generates a stronger entrepreneurial environment, stimulating students' entrepreneurial interests and enthusiasm as well as influencing their entrepreneurial behavior positively (Hou et al, 2019). Moreover, Balder et al (2020) indicated that EE encourages students to pursue self-employment after graduation. It has been demonstrated empirically that EE has a positive influence on the development of EI (Ndofirepi, 2020;Efrata et al, 2021;Hassan et al, 2022).…”
Section: Entrepreneurship Education and Entrepreneurial Intentionmentioning
confidence: 99%
“…In addition to its direct impact, SE can also mediate the link between EE and EI. Studies have found that EE boosts SE among entrepreneurs (Balder et al., 2020; Nuseir et al., 2020), which in turn, augments their intention to engage in entrepreneurial activities (Adu et al., 2020; Bagheri, 2018). Moreover, empirical studies have shown EE to be among the most important predictors of SE in becoming an entrepreneur (Arshad et al., 2018; Ayu et al., 2020; Suratno & Kusmana, 2019), which indicate that entrepreneurship courses and programs boost SE (Jiang et al., 2017; Lim et al., 2021).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable or IV is a binary class where the value of class 1 representing whistleblowing intention while 0 for not whistleblowing. The independent variables (IVs) used to construct the whistleblowing classification model, as outlined in Table 2, were adapted from the Theory of Planned Behaviour [18,19].…”
Section: Class Label Whistleblowing Intention 1-whistleblowing 0-not ...mentioning
confidence: 99%